Jerky/Earthbound facilitates cell-specific Wnt/Wingless signalling by modulating ?-catenin-TCF activity. - Benchabane, H.; Xin, N.; Tian, A.; Hafler, B.P.; Nguyen, K.; Ahmed, A.; Ahmed, Y. (The EMBO Journal, 2011)
Wnt/Wingless signal transduction directs fundamental developmental processes, and upon hyperactivation triggers colorectal adenoma/carcinoma formation. Responses to Wnt stimulation are cell specific and diverse; yet, how cell context modulates Wnt signalling outcome remains obscure. In a Drosophila genetic screen for components that promote Wingless signalling, we identified Earthbound 1 (Ebd1), a novel member in a protein family containing Centromere Binding Protein B (CENPB)-type DNA binding domains. Ebd1 is expressed in only a subset of Wingless responsive cell types, and is required for only a limited number of Wingless-dependent processes. In addition, Ebd1 shares sequence similarity and can be functionally replaced with the human CENPB domain protein Jerky, previously implicated in juvenile myoclonic epilepsy development. Both Jerky and Ebd1 interact directly with the Wnt/Wingless pathway transcriptional co-activators ?-catenin/Armadillo and T-cell factor (TCF). In colon carcinoma cells, Jerky facilitates Wnt signalling by promoting association of ?-catenin with TCF and recruitment of ?-catenin to chromatin. These findings indicate that tissue-restricted transcriptional co-activators facilitate cell-specific Wnt/Wingless signalling responses by modulating ?-catenin-TCF activity.